Re-appraisal of the role of the state in small economies - Venner, K. Dwight ([Eastern Caribbean Central Bank] BasseterreKN, 1991)
Gives an overview of the role of the state. Previews the various functions of the state and examines them in their national and OECS context. Looks briefly at some aspects of the managerial state in the context of the developmental strategies of OECS countries. Covers such aspects as fiscal, monetary and trade policies.